PETS-QSDS in Sub-Saharan Africa : A Stocktaking Study - Gauthier, Bernard (World Bank, Washington, DC, 2017)
This study examines Public Expenditure Tracking Survey (PETS) and Quantitative Service Delivery Survey (QSDS) carried out in Africa with the objective of assessing their approaches, main findings, and contributions. Section 2 investigates the context, motivations, and objectives of PETS and QSDS that have been carried out in Sub-Saharan Africa. Section 3 examines the institutional arrangements for resource allocation and service delivery in social sectors. Section 4 presents some of the main findings of tracking surveys. Section 5 analyzes methodological approaches used in previous tracking surveys in order to identify factors that could explain the difference in past surveys' success, and identify potential methodological harmonization. Section 6 presents a series of good practice principles that arise from past experience, and discusses how they could be implemented. Section 7 proposes potential future surveys and endeavors.